Adiposity predicts low cardiorespiratory fitness in individuals with metabolic diseases. (December 2018) - Shaw, Andy; Houghton, David; Hallsworth, Kate; Jakovljevic, Djordje G.; Trenell, Michael I.; Cassidy, Sophie
Abstract: Cardiorespiratory fitness (CRF) is impaired in those with metabolic diseases and strongly predicts mortality. We found that adiposity, not glycaemic control or disease type, is the strongest predictor of low CRF in those with metabolic diseases. We discuss how adiposity and metabolic health may relate to outcomes in obesity.